Ballistic resistance analysis of non-filled tank against fragment simulating projectile (FSP) / Mohd Rozaiman Aziz ... [et al.] - Aziz, Mohd Rozaiman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
This paper presents the ballistic impact study for the non-filled aluminum tank. The objective was to determine the ballistic limit for front tank wall and rear tank wall. The tank was impacted with fragment simulating projectile (FSP) with various velocities range from 239 m/s up to 556 m/s. The aluminum tank was 3 mm thick, 150 mm wide and 750 mm long. The ends of tank were closed with two Polymethyl methacrylate (PMMA) windows which fixed to the tank with four steel bars. The test was conducted at the Science and Technology Research Institute for Defense (STRIDE) Batu Arang, Selangor. The results showed that the ballistic limit for the front tank wall and rear tank wall was 257.7 m/s and 481 m/s, respectively. In addition, the study present the correlation of the impact velocity towards residual velocity, damage area, wall deflection, velocity drop and energy absorbed.